A Phenomenological Study of Women’s Lived Experiences as Incest Survivors - Abigail Soesana; Andrian Pramadi; Endah Triwijati (Journal of Educational, Health and Community Psychology, 2026)
Sexual violence against women remains a critical concern in Indonesia, and incest is among its most severe forms. Records from Komnas Perempuan indicate a high prevalence; in 2018, 1,210 incest cases were documented, with biological fathers and uncles frequently reported as perpetrators. Incest often results in profound psychological and social consequences, including stigma, ruptured trust, anxiety, depression, and prolonged trauma. This study examined the lived experiences of women who survived incest and the ways they rebuilt their lives following trauma. Grounded in Heideggerian interpretive phenomenology, the research explored survivors’ meaning-making within their relational and sociocultural worlds. Two participants were recruited through purposive sampling. In-depth interviews were transcribed verbatim and analyzed using interpretive thematic analysis. Ten interpretive findings were generated and organized into two overarching categories—experiences as victims and experiences as survivors—supported by eight core themes. The findings highlight complex struggles alongside emerging agency and resilience, informing survivor-centered recovery frameworks and trauma-informed community interventions.